DISCOVERY AND CHARACTERIZATION OF INHIBITORS OF BACTERIAL METABOLISM - Zlitni, Soumaya (My University, 2014)
The alarming rise of antibacterial drug resistance and the dwindling supply of novel antibiotics highlight the need for innovative approaches in combating bacterial infections. Traditionally, antibacterial drug discovery campaigns have largely been conducted in rich media. Such growth conditions are not representative of the host environment and render many metabolic pathways, otherwise needed for survival and infection, dispensable. Such pathways have been overlooked in conventional drug discovery campaigns despite their validity as potential antibacterial targets. The work presented in this thesis focuses on the development and validation of a screening strategy for the identification and mechanism of action determination of novel inhibitors of metabolic pathways in bacteria under nutrient-limited conditions. This screen led to the identification of MAC168425, MAC173979 and MAC13772 as inhibitors that target glycine metabolism, p-aminobenzoic acid biosynthesis and biotin biosynthesis, respectively. Moreover, it established this approach as a general platform that can be applied for different organisms with synthetic or natural product libraries. Additional mechanistic studies of the biotin biosynthesis inhibitor, MAC13772, resulted in solving the crystal structure of BioA in complex with MAC13772. Analysis of the co-structure confirmed our proposed mode of inhibition and provided information for strategies for rational drug design. Investigation of the antibacterial activity of MAC13772 revealed its potency against a number of pathogens. Furthermore, we show how MAC13772 acts synergistically with rifampicin in clearing growing mycobacterial cultures. The potential of this inhibitor as a lead for preclinical pharmacokinetic studies and for antibacterial drug development is discussed. We also discuss our current efforts to develop a metabolomic platform for the characterization of novel antibacterials that can be used in concert with our current approach to chart the metabolic response of bacteria to chemical perturbants and to generate testable hypotheses regarding the mode of action of novel inhibitors of bacterial metabolism.
CHEMICAL GENETICS AND METABOLIC SUPPRESSION PROFILING IDENTIFY NOVEL INHIBITORS OF BACTERIAL BIOSYNTHETIC PATHWAYS
Keywords: Antibiotic, Drug discovery, Chemical Biology, Bacteria, Metabolism, Mechanism of action, Small molecule inhibitors, High-throughput screening, Enzymology, Genetics, Bacterial physiology